ANALISIS PENGGUNAAN DANA PENANGGULANGAN BENCANA PADA BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN MELAWI - Hermansyah Putra Pane; Fahmi, Muhammad; Rusliyawati, Rusliyawati (Universitas Lancang Kuning, 2024)
The aim of the research is to analyze the Regional Disaster Management Agency (BPBD), which is a regional government agency that has the task of implementing disaster management at the provincial, district or city level, in accordance with the rules set by the National Disaster Management Agency (BNPB). This research method uses qualitative research methods by collecting data from direct interviews and field observations. The results of this research show that disasters that occur during 2023 are dominated by floods and fires, but the most frequent ones are floods. BPBD Melawi Regency has used disaster management funds as best as possible, but is experiencing problems in carrying out its activities due to the very limited budget. The implications of the condition of disaster management funds at BPBD Melawi Regency in 2024 have improved from the previous year. This has had a positive impact on the Melawi Regency BPBD to carry out its comprehensive disaster management program from the pre-disaster, emergency response and post-disaster stages.